RESPOSTAS GERMINATIVAS DE LACTUCA SATIVA E UROCHLOA BRIZANTHA EXPOSTAS A SURFACTANTES CATIÔNICOS, ANIÔNICOS E NEUTROS. - FERNANDES, Simone Yasuda,; ARAÚJO, Débora,; SANTOS, Jaqueline Silva,; PONTES, Montcharles Silva,; ARRUDA, Gilberto,; SANTIAGO, Etenaldo F., (ANAIS DO ENIC, 2023)
-